Biocompatibility of a decellularized liver scaffold in studies in vitro - Yurkevich, Mariya Yu.; Dubko, Andrei D.; Nizheharodava, Darya B.; Labai, Maryna V.; Zafranskaya, Marina M. (Experimental Biology and Biotechnology, 2021)
The development of multicomponent threedimensional structures based on decellularized tissue is a perspective alternative for organ transplantation in end-stage liver disease. The technology of rat liver decellularization is presented which consist in sequential perfusion of organ through the portal vein and use of 0.1 % sodium dodecyl sulfate as an active solution. The absence of the cytotoxic effect of decellularized scaffolds on allogeneic splenocytes and multipotent mesenchymal stromal cells was established. The obtained liver scaffolds are biocompatible in cells cultures and correspond criteria for cell carriers.